Protocol to computationally average confocal images of zebrafish lymphatic vessels to identify phenotypes - Hannah Arnold; Virginia Panara; Amin Allalou; Katarzyna Koltowska (STAR Protocols)
Summary: Characterization of zebrafish mutants is routinely time consuming as morphological phenotypes can be subtle or variable, thus hampering robust quantification. Here, we present a protocol to identify the overall phenotype by overlaying images of lymphatic vessels acquired from multiple zebrafish embryos of a genetic background. We describe steps for preparing samples, obtaining confocal images, and their computational alignment. In addition, we supply sample images for testing.For complete details on the use and execution of this protocol, please refer to Arnold et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.